2024
DOI: 10.1039/d3ee03818a
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable high-temperature ionic thermoelectric performance induced by graphene in gel thermocells

Cheng-Gong Han,
Yong-Bin Zhu,
Lijuan Yang
et al.

Abstract: Gels thermocells employing redox couple ions as carriers can convert heat into electricity, playing an important role in low-grade heat harvesting. However, a major challenge is maintaining the high ionic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
2

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
2
2
Order By: Relevance
“…29 The voltage of the gel-device reached 1.55 V, comparable to the reported values, e.g. , 0.025 V (Jiang), 37 0.12 V (Han), 33 2.2 V (Han), 16 and 2.8 V (Li). 28 In addition, the assembled gel-device could power a red LED at 313 K and Δ T = 5 K without a voltage booster (Fig.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…29 The voltage of the gel-device reached 1.55 V, comparable to the reported values, e.g. , 0.025 V (Jiang), 37 0.12 V (Han), 33 2.2 V (Han), 16 and 2.8 V (Li). 28 In addition, the assembled gel-device could power a red LED at 313 K and Δ T = 5 K without a voltage booster (Fig.…”
Section: Resultssupporting
confidence: 87%
“…3(c)). The normalized energy density of 3.4 J m −2 K −2 (2 h) was higher than the reported values of 0.37 and 0.99 J m −2 K −2 (2 h, Li), 28,29 0.19 J m −2 K −2 (1 h, Han), 33 and 1.43 J m −2 K −2 (1 h, Jiang), 37 as shown in Table S3 (ESI†). The decreased resistance from 7.5 to 5.0 kΩ indicated that the internal resistance of the i-TE-EC cell decreased after adding additives, corresponding to an increased σ i (Fig.…”
Section: Resultscontrasting
confidence: 73%
See 3 more Smart Citations